2020
DOI: 10.1017/s1366728920000127
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive control in interpreters: Assessing the impact of training and experience on working memory

Abstract: The adaptive control hypothesis predicts adaptation of control mechanisms as a response to intensive language use in bilinguals. The present study aims to investigate this hypothesis in two memory experiments with professional and student interpreters. In experiment 1, we compared a group of interpreting students to translation students using a reading span task to test working memory (WM) and a digit span task to test short-term memory (STM). In experiment 2, we added a group of professional interpreters and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The Simon task is used in the current study design to examine general response inhibition in the student groups compared to the professional interpreters and to replicate the study. In recent studies on different EF mechanisms, professional interpreters performed better than younger noninterpreting students both in working memory (Nour et al, 2020) and better than both interpreting and non-interpreting students on incongruent trials in the Attention Networks Task (Nour et al, 2019). These better performances of professionals showed themselves most pronounced in the accuracy scores; suggesting that while younger participants may rely more on speed, older adults might focus more on accuracy (Forstmann et al, 2011).…”
Section: The Present Studymentioning
confidence: 90%
See 1 more Smart Citation
“…The Simon task is used in the current study design to examine general response inhibition in the student groups compared to the professional interpreters and to replicate the study. In recent studies on different EF mechanisms, professional interpreters performed better than younger noninterpreting students both in working memory (Nour et al, 2020) and better than both interpreting and non-interpreting students on incongruent trials in the Attention Networks Task (Nour et al, 2019). These better performances of professionals showed themselves most pronounced in the accuracy scores; suggesting that while younger participants may rely more on speed, older adults might focus more on accuracy (Forstmann et al, 2011).…”
Section: The Present Studymentioning
confidence: 90%
“…Inhibition is considered as a general control process that is shared across other EF processes such as switching-specific and updating-specific control (Miyake et al, 2000;Friedman, 2016). Previous studies on Inhibition in interpreters showed mixed results which could be due to the differences in study designs, task specificity or linguistic backgrounds of the participants (Yudes et al, 2011;Timarová et al, 2014) (for review see Nour et al, 2020). The overall results showed no advantage when comparing interpreters to other bilingual groups (Dong and Xie, 2014;Babcock and Vallesi, 2017;.…”
Section: Inhibition In Interpretersmentioning
confidence: 98%
“…Simultaneous interpreting training yields enhancement in verbal short-term memory (while translation training or training in a variety of non-language subjects does not have memory benefits) (Babcock et al, 2017). Nonetheless, other studies have found that both translation and interpreting training enhance verbal WM (reading span), but not short-term memory (digit span) (Nour et al, 2020). These different results might be related to the length of training and employing different WM tasks (Nour et al, 2020).…”
Section: Wm and Predictionmentioning
confidence: 99%
“…Expert-novice comparison has been a popular approach to research on interpreting, and has been used to investigate differences in cognitive control between people having different amount of interpreting experience. In this regard, Nour et al (Nour et al, 2020) investigate how professional and student interpreters differ in working memory. Using a reading span task to test WM and a digit span task to test short-term memory (STM), they tested a group of interpreting students, a group of translation students, and a group of older professional interpreters (on average 30 years older than the students).…”
mentioning
confidence: 99%
“…The second group includes two papers that are related to cognitive load, with Mårtensson and colleagues (Mårtensson, Eriksson, Bodammer, Lindgren, Johansson, Nyberg and Lövdén, 2020) investigating the brain basis of foreign language learning aptitude in interpreters, and Tiselius and Sneed (Tiselius & Sneed, 2020) cognitive load as reflected in gaze and eye-movements in dialogue interpreting. The third group, the remaining four papers, are related to language control and cognitive control in interpreting, with Dong and Li (Dong & Li, 2020) proposing an overall account in their attentional control model, Hervais-Adelman and Babcock (Hervais-Adelman & Babcock, 2020) focusing on the neurobiology of SI, Nour et al (Nour, Struys & Stengers, 2020) investigating the impact of interpreting experience on WM, and García et al (García, Muñoz & Kogan, 2020) reviewing the impact of SI experience on cognitive control.…”
mentioning
confidence: 99%